Reforming Education. Governance Through Local Capacity-building. A Case Study of the "Learning Locally" Programme in Germany. - Busemeyer, Marius; Vossiek, Janis (My University, 2015)
This report is an assessment of the programme "Lernen vor Ort" [LvO - "Learning Locally"] initiated by the German federal government in order to support the development of local governance structures in education. LvO ran between 2009 and 2014 in about 40 participating local governments, which were chosen in a competitive process. It aimed at promoting cooperation between local governments and civil society stakeholders, creating sustainable structures in educational monitoring, management and consulting as well as improving local capacities in knowledge management. Besides providing important background information on the German education system and the design of the LvO programme, this study engages in five detailed case studies of the implementation of the LvO programme in different local authorities. These studies are mainly based on approximately 90 interviews with local and national experts, and stakeholders. The main findings are that LvO can be regarded as a success due to the fact that it had a lasting and probably sustainable impact in the cases studied in this report, in particular with regard to those structures that produce concrete and visible outputs, such as educational monitoring. The case studies also reveal a number of local factors that influence the relative effectiveness of the implementation of the programme. Political leadership and support from the head of the local government are crucial, in particular during critical situations during the implementation. Furthermore, the impact of the programme was particularly positive, when the process of local implementation was characterised by clear communication strategies, broad stakeholder involvement in governing bodies and the implementation of concrete goals and projects. However, relative success also depended on important background factors such as local socio-economic conditions as well as financial and administrative capacities, which could not be adressed directly by the programme's goals.
Keywords: Bildungswesen; Gemeinde; Bildungsangebot; Kommunalpolitik; Erwachsenenbildung; Förderungsprogramm; Bildungspolitik; Kooperation; Fallstudie; Kommunale Bildungslandschaft; Informelle Bildung; Zivilgesellschaft